Factor demand in the healthy rice seed use in Boro and T. aman: A case study of Bangladesh - Islam, ASM Nazrul; Islam, SM Fakhrul (Bangladesh Journal of Agricultural Research, 2010)
Lack of healthy rice seed is considered as one of the most important constraints to rice production and productivity in Bangladesh. Healthy rice seed production and its use are pre-requisites for accelerate agricultural growth and this can play a leading role in bringing rural prosperity and economic transformation. Therefore, this study analyzes factors demand and elasticity of substitution of healthy rice seed. Data were collected from two different rice growing environments, namely Chuadanga and Gazipur. Primary data from 120 respondents were collected for Boro and T. Aman seasons. Allen Partial Elasticities were estimated for Boro and T.Aman rice for both the study areas. Healthy seed price was highly elastic and the results showed that an increase in the price of healthy seed would decrease its demand. The results showed that if the use of land increased then use of fertilizer, animal + power, seed, irrigation, and human labour would increase. In the T. Aman season, own price elasticities of all the factors had the correct signs. In Gazipur, with one percent increase in price, demand for land, animal power + mechanical power, seed, fertilizer and human labour would fall. The estimates on elasticity of substitution indicated that the best substitutes are land-seed, land-animal power plus mechanical power and land-labour in the Boro season. In the T.Aman season, the best substitutes were found to be land-irrigation in Chuadanga and land-animal power plus mechanical power, land-seed in Gazipur. Keywords: Healthy rice seed; boro; T.aman. DOI: 10.3329/bjar.v35i2.5893 Bangladesh J. Agril. Res. 35(2) : 297-312, June 2010